PENGARUH MEMBACA CEPAT TERHADAP KEMAMPUAN MEMAHAMI ISI TEKS BACAAN PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SDN BALONG BESUK DIWEK KABUPATEN JOMBANG - Sari, Endah; Sari, Ninuk Kumala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Indonesian language topic holds significant importance in the realm of education. Indonesian serves as the language of instruction in education and as a national language that must be taught from the start, including at elementary school level. Reading is an activity performed by individuals to grasp the message that the writer intends to communicate through language and text. This task enables individuals to access information presented in writing, based on their understanding or experience. Reading fundamentally involves striving to understand the text to interpret the meaning it conveys. The ability to read is a key component of the skills in Indonesian language and literature that must be mastered across all educational levels, including elementary school. This research seeks to examine and outline the intensive reading skills of students in grade IV at SDN Ceweng Diwek, categorized by high, medium, and low levels of learning interest. This research commenced due to the growing government focus on reading skills in Indonesia, which are still viewed as inadequate. Furthermore, several students continue to struggle with recognizing the main idea in the text and possess a restricted comprehension while reading. This research employs a qualitative approach. To evaluate the effect of speed reading on comprehension, the procedures involve organizing reading materials, creating test sheets with questions regarding the content, and instructing students to respond based on specified evaluation standards. The assessments given are presented as descriptive or essay-type questions.